PENGEMBANGAN MEDIA TOUCH AND PLAY 3D IMAGES MATERI PANCA INDERA KELAS IV SEKOLAH DASAR BERBASIS ADOBE FLASH - Ilmiah Nu Izzah (UNIVERSITAS PGRI MADIUN, 2017)
The use of teaching media in the 4th Grade of SDN Sukorejo IV, Sukerejo District, Pasuruan Regency has not been maximal, thus resulting the decreasing level of students’ motivation during the learning session. Then, it is needed an effort to escalate the students’ motivation in learning through the development and utilization of learning media. This research is conducted to produce The development of Touch and Play 3D Images Learning Media Based on Adobe Flash in the Five Senses Subject at 4th Grade of Elementary School, and to describes The students’ responses in the implementation of touch and play 3D images learning media based on Adobe Flash in the Five Senses Subject at 4th Grade of Elementary School. The research show that: The development of Touch and Play 3D Images learning media based on Adobe Flash in the Five Senses Subject at 4th Grade of Elementary School using the design of research and development stated by Borg and Gall. This design has 10 phases, but the researcher only applied 7 phases due to the phases which already modified, which are the potential and problems, data collection, design product, design validation, design revision, product testing, product revision. The Touch and Play 3D Images media in the Science Subject, The five senses Subject of 4th Grade students is part of the worthy to be used. Validity test held by the expert of the subject obtained the 87.5 % percentage within the Valid Category. The test of validity by the learning expert gets the percentage value of 97.2% included in the valid category. The average result of the student's response shows the percentage of 97.61% is included in either category. In conclusion, the Touch and Play 3D Images based on Adobe Flash in the five senses subject of 4th Grade Elementary Students can be considered as Valid as the learning media.